IFC Annual Report 2010 : Where Innovation Meets Impact, Volume 2. IFC Financials, Projects, and Portfolio 2010 - International Finance Corporation (Washington, DC: World Bank, 2012)
More than 200 million people in the developing world were out of work this year. Over 1 billion are hungry, while millions more are confronting the threat that climate change poses. The United Nations estimates that 884 million people don't have safe drinking water and more than 2.6 billion people lack basic sanitation. The population of the developing world will expand by a third over the next four decades, growth that will strain already weak infrastructure. In this environment, International Finance Corporation (IFC) is innovating to create opportunity where it's needed most. IFC committed a record $18 billion in fiscal year 2010, $12.7 billion of which was for own account. We invested in 528 projects, an 18 percent increase from FY09. Advisory Services portfolio comprised 736 active projects valued at more than $850 million, with annual expenditures totaling $268 million. Countries served by the International Development Association, or IDA, accounted for nearly half our investments 255 projects totaling $4.9 billion and more than 60 percent of Advisory Services expenditures. Sub-Saharan Africa accounted for 19 percent of our investment commitments and 25 percent of Advisory Services expenditures. The invested a record $1.64 billion in clean energy, leveraging $6.8 billion, while climate change related projects grew to 15 percent of the value of our Advisory Services portfolio. The investments in microfinance rose 10 percent to $400 million, expanding microfinance portfolio to $1.2 billion.